Keragaman Genetik Lima Populasi Gyrinops verstegii di Lombok menggunakan Penanda RAPD - AYPBC Widyatmoko; Rizki Diah Afritanti; Taryono Taryono; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2009)
Gyrinops verstegii is one of the species which produce high economic value of gaharu (agarwood). The objectives of this research were to estimate genetic diversity within and among populations, investigate distribution of genetic diversity, and genetic relationship among five populations of G. Verstegii. Leaf samples were taken from five populations of G. Vertegii in Lombok, NTB,. Genetic diversity was analyzed using 21 selective primers out 200 primers. A total of 42 polymorphic loci were detected. Mean of genetig diversity was 0.288, and genetic distance betwen populations was 0.148. The Proportion of 85.24 % of genetic diversity was distributed within population, and the remaining 14.76 % was distributed between populations. Based on cluster analysis, the five populations were separated into two major group consisted of Pusuk Pohon Induk, Pusuk Sumber Benih, and Mantang I. The second group consisted of Mantang Pohon Induk and Mantang II. Collecting genetic materials for conservation and tree improvement program should be focused on the materials within population and each group (regent) should be a representative of at least one population.